Leaf Cuticle Variations in Amaranthus spinosus as Indicators of Environmental Pollution (Biological Sciences - PJSIR, 2007)
. I n vest i gat i on of th e l eaf epidermal characteristics of Amaranthus spinosus from poll u ted and non-pol l uted populations revealed that the stomata I pores of the leaves of the plants of the poll uted  areas were c l osed whereas those of the non-poll uted areas were open  Mean len gh t x mean w id th of stomata I pores on th e upper l ea f su rface were 0.86µm x 0.43 tm and 1 . 23  Lill x  0.45 µm on the lower  leaf surface of th e non  poll uted  mi croh abi tats. A lso, the  lea ves of  the pol l uted popu lation were sma ll er than those of the n on-poll uted population . The avernge l eaf area of the pla nts of the polluted population was 7.64 cm' as agai nst 1 2 . 1 3 cm' of the plants of the non-poll uted  areas. The resu l ts were attri buted  to the combi ned  effects of ai r poll utant  that predomi n ated  roadsides  from where  the samples were taken.Thus, i t is i nferred that thi s plant could serve as bio-i ndicator of a i r poll u tion .